The Abolition Of The Death Penalty: A Comparative View From Syariah And Global Perspective - Norman Zakiyy Chow Jen-T'Chiang (Universiti Sains Islam Malaysia, 2024)
It has become commonplace in the warongs, kopitiams and cafes of the nation (and abroad) to hold discussion on the right of every human being to life. In brief; the right referred to is that of a convict of not to be executed in whatever methods 'in accordance to law. " The mood and temper of the public in regards to the treatment of certain heinous crimes and criminals is one of the most unfailing tests to the civilization of any country. Hence, this paper attempts to understand the concerns raised.